Increasing Frequencies of Antibiotic Resistant Non-typhoidal Salmonella Infections in Michigan and Risk Factors for Disease - Mukherjee, Sanjana; Anderson, Chase M.; Mosci, Rebekah E.; Newton, Duane W.; Lephart, Paul; Salimnia, Hossein; Khalife, Walid; Rudrik, James. T.; Manning, Shannon D. (Frontiers in Medicine, 2019)
Non-typhoidal Salmonella (NTS) are important enteric pathogens causing over 1 million food-illnesses in the US annually. The widespread emergence of antibiotic resistance in NTS isolates has limited the availability of antibiotics that can be used for therapy. Since Michigan is not part of the FoodNet surveillance system, few studies have quantified antibiotic resistance frequencies and identified risk factors for NTS infections. We obtained 198 clinical NTS isolates via active surveillance at four Michigan hospitals from 2011 to 2014 for classification of serovars and susceptibility to 24 antibiotics using broth microdilution. In all, the 198 isolates belonged to 35 different serovars with Enteritidis (36.9%) predominating followed by Typhimurium (19.5%) and Newport (9.7%), though the proportion of each varied by year, residence, and season. The number of Enteritidis and Typhimurium cases was higher in the summer, while Enteritidis cases were significantly more common among urban versus rural residents. A total of 30 (15.2%) NTS isolates were resistant to ≥1 antibiotic and 15 (7.5%) were resistant to ≥3 antimicrobial classes; a significantly greater proportion of Typhimurium isolates were resistant compared to Enteritidis isolates and an increasing trend in the frequency of tetracycline and multidrug resistance was observed over the four-year period. Resistant infections were associated with longer hospital stays as the mean stay was 5.9 days for patients with resistant isolates relative to 4 days for patients infected with susceptible isolates. Multinomial logistic regression indicated that infection with serovars other than Enteritidis (Odds ratio (OR): 3.8, 95% confidence interval (CI): 1.23-11.82) as well as infection during the fall (OR: 3.0; 95% CI: 1.22-7.60) were independently associated with resistance. Together, these findings demonstrate the importance of surveillance, monitoring resistance frequencies, and identifying risk factors that can aid in the development of new prevention strategies.